2020
DOI: 10.1101/2020.06.04.133462
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A simple and effective F0 knockout method for rapid screening of behaviour and other complex phenotypes

Abstract: Hundreds of human genes are associated with neurological diseases, but translation into tractable biological mechanisms is lagging. Larval zebrafish are an attractive model to investigate genetic contributions to neurological diseases. However, current CRISPR-Cas9 methods are difficult to apply to large genetic screens studying behavioural phenotypes. To facilitate rapid genetic screening, we developed a simple sequencing-free tool to validate gRNAs and a highly effective CRISPR-Cas9 method capable of converti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 87 publications
(101 reference statements)
4
12
0
Order By: Relevance
“…This finding is consistent with a recent study noting variable mutagenic efficiency of crRNAs [37]. We also compared the site of injections (cytoplasm vs yolk) since a recently published work using a similar approach performed injections exclusively into the yolk to examine behavioral phenotypes [32]. Our results showed that although three dgRNP injections into either site were both highly efficient, their cytoplasmic injections were slightly more consistent in phenocopying homozygous stable mutant phenotypes.…”
Section: Injections Of Single Vs Triple Dgrnps Per Genesupporting
confidence: 89%
See 1 more Smart Citation
“…This finding is consistent with a recent study noting variable mutagenic efficiency of crRNAs [37]. We also compared the site of injections (cytoplasm vs yolk) since a recently published work using a similar approach performed injections exclusively into the yolk to examine behavioral phenotypes [32]. Our results showed that although three dgRNP injections into either site were both highly efficient, their cytoplasmic injections were slightly more consistent in phenocopying homozygous stable mutant phenotypes.…”
Section: Injections Of Single Vs Triple Dgrnps Per Genesupporting
confidence: 89%
“…While dgRNP-based mutagenesis utilizing chemically synthesized crRNAs have been shown to efficiently disrupt gene function in F0 zebrafish even as single dgRNP injections [31][32][33][34][35][36][37], it is becoming clear that the efficacy of target gene disruption depends on the mutagenic ability of each designed crRNA, as also suggested by the recent report showing variable efficiency of synthetic crRNAs in gene editing [37]. As such, injection of single dgRNPs per gene can lead to varied mutagenesis efficiency, resulting in variable and incosistent phenotypic observations across crRNAs targeted to the same gene in injected F0 animals.…”
Section: Injections Of Single Vs Triple Dgrnps Per Genementioning
confidence: 99%
“…F0 mutagenesis using CRISPR has recently emerged as a powerful tool in Xenopus and zebrafish, and mosaic crispants generated by targeted injections allow simultaneous observation of wild-type and crispant cellular phenotypes so that observations are automatically staged and synchronized (Aslan et al, 2017; Kakebeen et al, 2020; Kroll et al, 2021; Szenker-Ravi et al, 2018; Willsey et al, 2020). We therefore labeled the neural plate by injection of fluorescent reporters into both dorsal blastomeres at the 4-cell stage, and then injected a mixture of shroom3 -targeted sgRNA, Cas9 protein, and membrane-BFP mRNA into one dorsal blastomere of 8-cell stage embryos to generate mosaic crispants ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We reasoned that directly injecting PCR amplified linear DNA with short homology arms (~35bp) could be highly effective since these donors are relatively small (~780 bp) compared to plasmids (several kbs) , and therefore a small quantity of donors (~10 ng/ul) will provide a large number of molecules (~20 nM) available to engage the HDR machinery following the Cas9 induced DSB. Building on recent improvements in CRISPR/Cas9 knock-in strategies, we used 5' biotinylated primers in order to limit in vivo concatemerization of the donor construct (Gutierrez-Triana et al, 2018), and synthetic sgRNAs were used to increase the efficiency of DSBs by Cas9 (Paix et al, 2015, Kroll et al, 2021, Hoshijima et al, 2019, Li et al, 2019. In addition, we utilized a monomeric streptavidin tagged Cas9 that has a high affinity to the biotinylated donor fragments to increase targeting efficiency (Gu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%